HUBUNGAN PENGUASAAN KOSAKATA DENGAN KEMAMPUAN MEMBACA CEPAT SISWA KELAS X IPA 6 SMA NEGERI 1 CURUP TAHUN PELAJARAN 2016/2017 - Gendis Siti Hatmanti; Syukri Hamzah; Agus Trianto (Universitas Bengkulu, 2017)
This research aims to examine the relationship of mastery of vocabulary with the fast reading ability students class X IPA 6 senior high school number 1 Curup. This type of research is correlation. The population of the research is the students of class X IPA 6 senior high school number 1 Curup. The sample of the research is the students of class X IPA 6 senior high school number 1 Curup totaling 30 students, taken using saturated sample technique. Data collection using test. The instrument test is performed with legibility test, validity test, reliabity test, different power test and difficulty test. Data analysis technique used is product moment correlation analysis. The result showed that: (1) mastery of the vocabulary of students as a whole got an average score of 69.11 included in the high category; (2) students overall reading ability (KEM) scored an average score of 224.87 which was included in the high category; (3) there is a significant correlation between vocabulary mastery with fast reading ability of student class X IPA 6 senior high school number 1 Curup equal to 0.53 (rh= 0.53 at significance level 5% with N= 30, rt= 0.36, and rg>rt). Based on the data of the research result can be concluded that there is a significant relationship between mastery of vocabulary with fast reading ability of student class X IPA 6 senior high school number 1 Curup in 2016/2017 academic year.